Ageism as an Invisible Sociocultural Phenomenon That Affects and Excludes the Care of the Elderly [Preconceito de Idade Como Um Fenómeno Sócio-Cultural Invisível Que Afecta E Exclui O Cuidado Das Pessoas Idosas] [Ageísmo Como Fenómeno Sociocultural Invisible Que Afecta y Excluye el Cuidado de Personas Mayores] - Pavez-Lizarraga, A (Universidad de Chile - Centro Interdisciplinario de Estudios en Bioetica, 2021)
Ageism in old age has been related to the social imaginary, responsible for maintaining prejudices and stereotypes towards older people. Prevailing as a common phenomenon in westernized countries like Chile, replicating an image of old age full of deficiencies and bodily deterioration. This article reflects on the phenomenon of ageism that promotes behaviors that exclude older people from life in society and from formal care. For this, it will be contextualized on the imaginaries that predominate in Chilean society about old age, and that transversally affect the family, institutions and professions; secondly, some explanatory theories about ageism will be described to better understand the phenomenon and its generational impact, and finally, about the initial abandonment of the elderly during the Covid-19 pandemic as a result of State ageism. Making this issue visible favors informed social debate and the promotion of new public policies in favor of the inclusion of older people. © 2021, Universidad de Chile - Centro Interdisciplinario de Estudios en Bioetica. All rights reserved.